Pyramidal and corticospinal synaptic effects over reticulospinal neurones in the cat. - Canedo, A (1993)
1. The spontaneous activity of 103 precruciate neurones (fifty-eight activated antidromically from the pyramidal tract but not from the corticospinal tract, PTNs; forty-five activated from both sites, CSNs) was used to trigger the average of the intracellularly recorded synaptic noise in 294 reticulospinal neurones (RSNs). These RSNs were recorded in the nucleus reticularis gigantocellularis of the contralateral medial bulbar reticular formation (NRGc) in chloralose-anaesthetized cats. 2. Twelve pyramidal tract neurones (six CSNs) were tested with a single RSN, twenty-six (10 CSNs) with two RSNs each, thirty (13 CSNs) with three RSNs each, and thirty-five (16 CSNs) with four RSNs each. Postsynaptic potentials were observed in the averages generated by twenty PTNs and fifteen CSNs. 3. The only synaptic effect produced by both PTNs and CSNs upon RSNs in our sample was excitatory, and in none of the tested cases (n = 15) were any changes found in the amplitude, shape, or duration of the excitatory postsynaptic potentials (EPSPs) after injection of depolarizing or hyperpolarizing currents. This suggests that the synapses are probably located at the distal dendrites. 4. Recording of the presynaptic spike allowed separation of the conduction time and synaptic delay from the total latency. According to our data there appear to be two different types of excitation of corticofugal neurones over RSNs: a monosynaptic effect produced by both PTNs and CSNs, and a disynaptic effect produced by PTNs but not by CSNs. The disynaptic EPSPs had statistically significant slower rise times and longer widths than the monosynaptic EPSPs.